MERETAS GLASS CEILING: KORELASI DRAMA KOREA “QUEEN WOO” DAN TEKS 1 TIMOTIUS 2:11-12 SERTA IMPLIKASINYA TERHADAP KEPEMIMPINAN PEREMPUAN - Saputra, Jefri Andri (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2025)
This article aims to break down the hidden barriers that make it difficult for women to become leaders like men. Gender equality has provided opportunities for men and women to receive education and empowerment, but women still experience obstacles in becoming leaders. The author responds to this problem by analyzing the Korean drama "Queen Woo" and the text of 1 Timothy 2:11-12 using the revised correlation approach. The author finds that the text of 1 Timothy 2:11-12 is Paul's sensitivity because of the honor and shame culture. Paul's command is an effort to restore the honor of men and women according to the values ​​and standards of patriarchal honor. Men drew their honor because of their work, and women drew their honor because of their manners. The drama Queen Woo shows the superior character to fight against the male monopoly on superiority. The author recommends that the church and society deconstruct the patriarchal legacy of the concept of honor and its relationship to gender. Women also need to be respected and their superiority recognized. Men and women must get equal superiority factually and through social recognition and respect.